Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
[tex]f(x) = x + 6 \\ f( - 2) = - 2 + 6 = 4 \\ f(0) = 0 + 6 = 6 \\ f(5) = 5 + 6 = 11[/tex]
Answer:
The answer is 4, 6 and 11 when x = (-2), 0 and 5 respectively
Step-by-step explanation:
Given;
- we are given an equation x + 6
- When, x = (-2), 0 and 5
Now,
f(x) = x + 6
For x = (-2)
f(-2) = -2 + 6
f(-2) = 4
For x = 0
f(0) = 0 + 6
f(0) = 6
For x = 5
f(5) = 5 + 6
f(5) = 11
Thus, The answer is 4, 6 and 11 when x = (-2), 0 and 5 respectively
-TheUnknownScientist 72
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.